Walking and talking with volunteers: what does walking offer the study of volunteering, space and place?. (2nd July 2020) - Daly, Siobhan; Allen, Michele
Abstract: The walking interview is used to explore the lived experiences and meanings individuals attach to place(s). Despite scholarly interest in place and volunteering, attention to the walking interview is lacking. This article presents an exploratory study, which invited five volunteers to participate in a walking interview. Our aim is to discuss the walking interview to expand the range of methodologies employed in research on volunteering, particularly volunteering and place. The walking interview has novel implications for the conceptualization of volunteers and for the meanings individuals identify in their volunteer experience(s). Volunteers can be conceptualized as mobile subjects to explore the implications of physiological movement in place for the volunteer experience. Walking can unearth the significance of emotions and memories to volunteers' negotiation of the 'everyday politics' of volunteering. The mobility of people and objects in sites of volunteering are salient as they reveal embodied aspects of the volunteer experience.